Review of the assessment of two stocks of Antarctic minke whales (eastern Indian Ocean and western South Pacific) - Murase, Hiroto; Palka, Debra; Punt, Andre; Pastene, Luis; Kitakado, Toshihide; Matsuoka, Koji; Hakamada, Takashi; Okamura, Hiroshi; Bando, Takeharu; Tamura, Tsutomu; Konishi, Kenji; Yasunaga, Genta; et al. (J. Cetacean Res. Manage., 2020)
An in-depth assessment of an eastern Indian stock (I-stock) and a western South Pacific stock (P-stock) of Antarctic minke whales distributed between 35°E and 145°W was carried out by the Scientific Committee of the International Whaling Commission (IWC/SC) from 2001 to 2014 using data mainly collected from 1985 to 2004. This paper is a synthesis and summary of the outcomes of that assessment, although research on this species has been ongoing since 2014. The assessment integrates information from a wide range of topics including systematics, survey methods, direct catches, population structure, abundance, spatial distribution, biological information, population dynamics, species interactions, pollutants and interactions with marine debris. At least two stocks (I-stock and P-stock) are found between 35°E–145°W, with a soft boundary between 100°E and 165°E. Two sets of agreed circumpolar estimates of abundance from IWC assessment cruises (termed ‘CPII’ – 1985/86–1990/91, and ‘CPIII’ – 1991/92–2003/04) were obtained; a null hypothesis of no change in overall abundance between CPII and CPIII was not rejected. The results of a Statistical Catch-at-Age Analysis (SCAA) applied to the two stocks revealed that (1) abundance increased from 1930 until the mid-1970s, and declined over the period from the mid-1970s until the late-1980s and (2) trends in abundance over the most recent 20 years were relatively flat for the I-stock but decreasing for the P-stock. Although the primary focus at the start of this assessment was to try to understand abundance trends during the 1985–2004 period, it expanded to increasing knowledge on the life history of this species. The assessment also advanced many aspects of analytical methods.